In vivo tracking of histone H3 lysine 9 acetylation in Xenopus laevis during tail regeneration. (24th February 2016) - Suzuki, Miyuki; Takagi, Chiyo; Miura, Shinichirou; Sakane, Yuto; Suzuki, Makoto; Sakuma, Tetsushi; Sakamoto, Naoaki; Endo, Tetsuya; Kamei, Yasuhiro; Sato, Yuko; Kimura, Hiroshi; Yamamoto, Takashi; et al.
Abstract : Xenopus laevis tadpoles can completely regenerate their appendages, such as tail and limbs, and therefore provide a unique model to decipher the molecular mechanisms of organ regeneration in vertebrates. Epigenetic modifications are likely to be involved in this remarkable regeneration capacity, but they remain largely unknown. To examine the involvement of histone modification during organ regeneration, we generated transgenic X. laevis ubiquitously expressing a fluorescent modification‐specific intracellular antibody (Mintbody) that is able to track histone H3 lysine 9 acetylation (H3K9ac) in vivo through nuclear enhanced green fluorescent protein (EGFP) fluorescence. In embryos ubiquitously expressing H3K9ac‐Mintbody, robust fluorescence was observed in the nuclei of somites. Interestingly, H3K9ac‐Mintbody signals predominantly accumulated in nuclei of regenerating notochord at 24 h postamputation following activation of reactive oxygen species (ROS). Moreover, apocynin (APO), an inhibitor of ROS production, attenuated H3K9ac‐Mintbody signals in regenerating notochord. Our results suggest that ROS production is involved in acetylation of H3K9 in regenerating notochord at the onset of tail regeneration. We also show this transgenic Xenopus to be a useful tool to investigate epigenetic modification, not only in organogenesis but also in organ regeneration. Abstract : After amputation, ROS are immediately produced near the amputation site and its production is sustained during tail regeneration. Acetylation of H3K9 is subsequently induced at the amputation site, in particular, in the notochord from 16 to 24 hpa.